2011
DOI: 10.1136/emermed-2011-200599
|View full text |Cite
|
Sign up to set email alerts
|

Doctors' working conditions in emergency care units in Germany: a real-time assessment

Abstract: Doctors working in emergency care units have to deal with highly unpredictable workloads and overtime work, and simultaneously should also care for patients and interact with a large number of different persons during each work shift. The findings of this study are useful in efforts to improve emergency medical care and doctors' working conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
1
9
0
2
Order By: Relevance
“…Similarly, Kee et al reported that consultants undertook more than 100 tasks an hour 15. This is higher than the 34 tasks per hour as reported by France et al 26 or 80 tasks per working day as reported by Mache et al 21…”
Section: Resultsmentioning
confidence: 87%
“…Similarly, Kee et al reported that consultants undertook more than 100 tasks an hour 15. This is higher than the 34 tasks per hour as reported by France et al 26 or 80 tasks per working day as reported by Mache et al 21…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies carried out in German hospitals analyzed doctors' working conditions and job satisfaction in various hospitals [26][27][28][29][30][31][32][33][34][35][36][37]. A number of studies focused on German emergency departments using surveys on the quality of medical treatment to evaluate hospital performance and working environments [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Für Deutschland gibt es nur eine limitierte Zahl aussagekräftiger Studien zu der Zeitaufteilung von Ärzt*innen und Pflegenden auf einzelne Tätigkeiten in der Notaufnahme. In einer Studie in 3 Berliner Notaufnahmen zeigten Mache et al [4], dass Ärzt*innen zwar 88 % ihrer Zeit in klinischer Arbeit mit Patientenbezug verbringen, diese jedoch in großem Umfang auch Aufgaben der internen Kommunikation, Dokumentation, Meetings und Administration umfasst [4]. Die tatsächliche Arbeitszeit in patientennaher Untersuchung und Diagnostik lag bei 10 % [4].…”
Section: Hintergrund Und Fragestellungunclassified
“…In einer Studie in 3 Berliner Notaufnahmen zeigten Mache et al [4], dass Ärzt*innen zwar 88 % ihrer Zeit in klinischer Arbeit mit Patientenbezug verbringen, diese jedoch in großem Umfang auch Aufgaben der internen Kommunikation, Dokumentation, Meetings und Administration umfasst [4]. Die tatsächliche Arbeitszeit in patientennaher Untersuchung und Diagnostik lag bei 10 % [4]. Ärzt*innen einer pädiatrischen Notfallambulanz waren bis zu 59 % der Zeit in direktem Patientenkontakt, mit ungefähr 20 min pro Patient*in, tätig [5].…”
Section: Hintergrund Und Fragestellungunclassified